The dynamics and determinants of social capital in the European Union and neighbouring countries. Summary: Sotsiaalkapitali dünaamika ja determinandid: EL vanade ja uute liikmesriikide ning nende naaberriikide võrdlus - Parts, Eve (Estonian Discussions on Economic Policy, 2013)
This empirical study investigates the dynamics and the determinants of social capital in Europe over the period 1990-2008, using empirical data from EVS. Methodologically, factor analysis and regression analysis are implemented. The analysis covers 20 Western-European countries, 10 new member states and 15 EU neighbouring countries. Comparison of the levels of social capital showed that, with few exceptions, the levels of social capital are lower in Eastern Europe as compared to the old member states in Western Europe. Regression results of the determinants of social capital showed that most influential factors of social capital are education and satisfaction with democracy. It follows that investments in educational system and improving democratization processes could increase the level of social capital as an important factor of economic development.